Upaya Mitigasi Kebakaran Hutan dan Lahan Melalui Program CSR Budidaya Madu Hutan Gambut PT Pertamina RU II Sungai Pakning - Anugrah, Ilham; Laksmono, Bambang (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Corporate Social Responsibility is social responsibility for companies as a real effort for companies to contribute to realizing the welfare of society. The incidence of forest and land fires in Riau, especially Bengkalis Regency, is a social issue that is a serious problem for the central and regional governments. The problem formulation of this research is how CSR Pertamina RU II Sungai Pakning involves the community in the process of mitigating forest and land fires. The aim of this research is to determine the process of forest fire mitigation through the CSR program of cultivating peat forest honey. The research method uses qualitative, because this research was conducted to determine, pay attention to and understand problems in social phenomena. The results of this research are that the Biene Honey Group is a pioneer in making people aware of honey seekers in the forest using traditional methods. In the future, it is hoped that PT. Pertamina RU II Sungai Pakning to be sustainable to continue the CSR program. as an effort to improve the welfare of the surrounding community.